Promoting moral growth through intra-group participation - Nelson, D. R. (Journal of business ethics, 1990)
Currently, an emphasis is being placed on the integration of ethical issues into the business curriculum. This paper investigates the viability of using student group interaction to induce an upward movement in the stages of moral development as advanced by Kohlberg. The results of a classroom experiment using graduate business law students suggest that formulating groups that mix stages of moral development can provide a robust environment for upward movement. In addition, the results suggest strategies for formulating effective groups, based upon entry levels as measured by the Defining Issues Test.